O02 Improving antimicrobial use in HSE older persons residential care facilities. (19th January 2023) - Shah, M; Clancy, A; Regan, M; Maher, A M; Armitage, S; Ryan, C; Mannion, C; Sheehan, P; Gallagher, O; Foran, R; Fagan, S; Donnelly, M; et al.
Abstract: Background: Antimicrobial use in Irish older persons residential care facilities (OP RCFs) is higher than in other European countries. In 2020/21, for the first time, an antimicrobial pharmacist (AMP) was appointed to each community healthcare organization (CHO) to monitor, develop and promote antimicrobial stewardship in community settings. Objectives: To establish baseline antibiotic use, develop antimicrobial stewardship tools for OP RCFs, promote best practice in relation to antimicrobial stewardship (AMS) and monitor trends in antimicrobial use in HSE (state-run) OP RCFs. Methods: A baseline point prevalence survey (PPS) of antimicrobial use was conducted across all HSE OP RCFs between October 2020 and August 2021. Following the survey, key national recommendations and AMS resources were developed in collaboration with the national Antimicrobial Resistance and Infection Control Programme. Feedback was provided to participating facilities by CHO AMPs with antimicrobial stewardship support and education for nursing and medical staff. In September 2021, monthly monitoring of antibiotic use was established in HSE OP RCFs in collaboration with local managers, to capture the proportion of antibiotics used for prophylaxis or treatment each month. Results: A baseline PPS of antimicrobial use in 2020/21 showed that 11.9% (528/4446) of residents were on a systemic antibiotic, with 6.3% on antibiotic prophylaxis. Urinary tract infection accounted for 51% of antibiotic prescriptions. Following the baseline PPS, CHO AMPs developed an AMS toolkit for OP RCFs, engaged with nursing and medical staff to communicate PPS results, AMS resources and support implementation of AMS recommendations. Subsequently, monthly self-reporting of antimicrobial use in HSE OP RCFs was commenced in September 2021 and showed a sustained decrease in antimicrobial use with 7.9% residents on an antibiotic in Quarter 2 2022, with 2.7% on antibiotic prophylaxis. Conclusions: Newly appointed CHO AMPs have successfully promoted AMS across HSE OP RCFs. Following audit, feedback, education, development and promotion of antimicrobial stewardship resources, there was a sustained decrease in the proportion of residents on antibiotics used for treatment and prophylaxis of infection.